2017
DOI: 10.1038/srep45944
|View full text |Cite
|
Sign up to set email alerts
|

Improving “color rendering” of LED lighting for the growth of lettuce

Abstract: Light plays a vital role on the growth and development of plant. On the base of white light with high color rendering to the benefit of human survival and life, we proposed to improve “color rendering” of LED lighting for accelerating the growth of lettuce. Seven spectral LED lights were adopted to irradiate the lettuces under 150 μmol·m−2·s−1 for a 16 hd−1 photoperiod. The leaf area and number profiles, plant biomass, and photosynthetic rate under the as-prepared LED light treatments were investigated. We let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 24 publications
1
44
1
Order By: Relevance
“…Light-emitting diodes (LED) technology is based on the use of electronic devices built with semiconductor materials which efficiently convert the electricity into light. The use of LED-based equipment allows the modulation of the intensity and the composition of the light spectrum [1], thus enabling the optimal lighting condition for a specific crop at each developmental stage to be set, optimizing plant growth in the most energy-efficient way [2]. Moreover, modern informatic tools allow the setting of complex light recipes, through the selection of the most appropriate spectral composition in a very accurate manner.…”
Section: Introductionmentioning
confidence: 99%
“…Light-emitting diodes (LED) technology is based on the use of electronic devices built with semiconductor materials which efficiently convert the electricity into light. The use of LED-based equipment allows the modulation of the intensity and the composition of the light spectrum [1], thus enabling the optimal lighting condition for a specific crop at each developmental stage to be set, optimizing plant growth in the most energy-efficient way [2]. Moreover, modern informatic tools allow the setting of complex light recipes, through the selection of the most appropriate spectral composition in a very accurate manner.…”
Section: Introductionmentioning
confidence: 99%
“…One of the critical steps of indoor plant cultivation is to find reliable light sources which can provide tunable light spectrum to fit different plant photoreceptors. Light emitting diodes (LEDs) with overwhelming advantages of energy saving, compactness, long lifetime, and environmental friendliness as well as controllable light colors have defeated conventional incandescent, metal‐halide, and fluorescent lamps as the major artificial light sources for plant cultivation . Compared with blue and red LEDs, the fabrication of far‐red‐emitting LEDs is relatively more difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The published literature sources have thus far not investigated using white LED lighting systems as a control group, and comparing the biomass increases under various different light conditions to this control. That which has been considered so far is to determine the optimized LED light for plant growth [19]. Han et al have indicated that Red, Yellow and Blue combinations with good "color rendering" is for the benefit of the growth of the plant [19].…”
Section: Background Prior Studies and Experimental Methodologiesmentioning
confidence: 99%